Ireland, Drama, and Social Decline: G. B. Shaw’s Man and Superman - McAteer, Michael (FOCUS: Papers in English Literary and Cultural Studies, 2012)
Although one of the most influential playwrights of the early twentieth century, and certainly the dominant intellectual figure in London theatre up to the Second World War, George Bernard Shaw has never acquired the same canonical status in the repertoire of Irish drama that was afforded his contemporaries John Millington Synge and Sean O’Casey. The sheer enormity of Shaw’s output from the 1880s to his death in 1956 offers a partial explanation for this, dwarfing as it does the wellmeaning industrious efforts of those dedicated to the Literary Revival in Ireland from the 1890s. Shaw himself amplified the view that the movement from which the Abbey Theatre grew in 1904 was a provincial affair, of little consequence in the much wider social transformations that had given rise to socialism as the new radical political philosophy to which his work was dedicated.